Symmetry-mediated quantum coherence of W5+ spins in an oxygen-deficient double perovskite - Shannon Bernier; Mekhola Sinha; Tyler J. Pearson; Peter V. Sushko; Paul H. Oyala; Maxime A. Siegler; W. Adam Phelan; Abby N. Neill; Danna E. Freedman; Tyrel M. McQueen (npj Quantum Materials)
Abstract Elucidating the factors limiting quantum coherence in real materials is essential to the development of quantum technologies. Here we report a strategic approach to determine the effect of lattice dynamics on spin coherence lifetimes using oxygen deficient double perovskites as host materials. In addition to obtaining millisecond T 1 spin-lattice lifetimes at T ~ 10 K, measurable quantum superpositions were observed up to room temperature. We determine that T 2 enhancement in Sr2CaWO6-δ over previously studied Ba2CaWO6-δ is caused by a dynamically-driven increase in effective site symmetry around the dominant paramagnetic site, assigned as W5+ via electron paramagnetic resonance spectroscopy. Further, a combination of experimental and computational techniques enabled quantification of the relative strength of spin-phonon coupling of each phonon mode. This analysis demonstrates the effect of thermodynamics and site symmetry on the spin lifetimes of W5+ paramagnetic defects, an important step in the process of reducing decoherence to produce longer-lived qubits.